A Double‐Blind, Randomized, Controlled Trial of Lovastatin in Early‐Stage Parkinson's Disease - Lin, Chin‐Hsien; Chang, Chin‐Hao; Tai, Chun‐Hwei; Cheng, Mei‐Fang; Chen, Yi‐Chieh; Chao, Ying‐Ting; Huang, Tse‐Le; Yen, Ruoh‐Fang; Wu, Ruey‐Meei (Movement disorders, 2021)
ABSTRACT Background Recent evidence indicates that lipophilic statins have a neuroprotective benefit in animal models of Parkinson's disease (PD). The objective of this study was to evaluate whether lovastatin has the potential to slow motor symptom progression in patients with early‐stage PD. Methods This double‐blind, randomized, placebo‐controlled trial enrolled 77 patients with early‐stage PD between May 23, 2017, and July 12, 2018, with follow‐up ending September 1, 2019. Lovastatin 80 mg/day or placebo with 1:1 randomization was administered for 48 weeks. Mean change in the parts I–III scores of the Movement Disorder Society–Unified Parkinson's Disease Rating Scale (MDS‐UPDRS), changes in the striatal dopamine uptake ratio measured by 18F‐dopa PET scan, and changes in PD medications between baseline and the week 48 visit were measured. Results Of the 77 randomized patients, 70 (90.9%) completed the study. There was a slightly beneficial trend of the MDS‐UPDRS motor score in the lovastatin group (−3.18 ± 5.50) compared with the placebo group (−0.50 ± 6.11); P = 0.14 adjusted for age, sex, disease duration, and baseline LEDD. Mean percentage change in the striatal 18F‐dopa uptake ratio deteriorated less in the lovastatin group than in the placebo group on the dominant side of caudate (1.2% ± 7.3% vs −7.1% ± 8.2%, P < 0.01) and putamen (2.3% ± 7.1% vs −6.4% ± 8.1%, P < 0.01). We found no between‐group differences in the change in part I or part II MDS‐UPDRS scores. Lovastatin was generally well tolerated. Conclusions Lovastatin treatment in patients with early‐stage PD was associated with a trend of less motor symptom worsening and was well tolerated. A future larger long‐term follow‐up study is needed to confirm our findings. © 2021 International Parkinson and Movement Disorder Society